Impact of Long-Term HFD Intake on the Peripheral and Central IGF System in Male and Female Mice - Guerra-Cantera, Santiago (Metabolites, 2020)
The insulin-like growth factor (IGF) system is responsible for growth, but also affects metabolism and brain function throughout life. New IGF family members (i.e., pappalysins and stanniocalcins) control the availability/activity of IGFs and are implicated in growth. However, how diet and obesity modify this system has been poorly studied. We explored how intake of a high-fat diet (HFD) or commercial control diet (CCD) affects the IGF system in the circulation, visceral adipose tissue (VAT) and hypothalamus. Male and female C57/BL6J mice received HFD (60% fat, 5.1 kcal/g), CCD (10% fat, 3.7 kcal/g) or chow (3.1 % fat, 3.4 kcal/g) for 8 weeks. After 7 weeks of HFD intake, males had decreased glucose tolerance (p < 0.01) and at sacrifice increased plasma insulin (p < 0.05) and leptin (p < 0.01). Circulating free IGF1 (p < 0.001), total IGF1 (p < 0.001), IGF2 (p < 0.05) and IGFBP3 (p < 0.01) were higher after HFD in both sexes, with CCD increasing IGFBP2 in males (p < 0.001). In VAT, HFD reduced mRNA levels of IGF2 (p < 0.05), PAPP-A (p < 0.001) and stanniocalcin (STC)-1 (p < 0.001) in males. HFD increased hypothalamic IGF1 (p < 0.01), IGF2 (p < 0.05) and IGFBP5 (p < 0.01) mRNA levels, with these changes more apparent in females. Our results show that diet-induced changes in the IGF system are tissue-, sex- and diet-dependent.